Contributions to the kinetics of the iodide–iodate test reaction for micromixing time calculation with extended incorporation models. (29th June 2021) - Arian, Elias; Pauer, Werner
Highlights: For the first time, the pure influence of ionic strength on the reaction rate constant k of the Dushman reaction was obtained using N a C l O 4 as a salt. A fifth-order reaction rate equation was identified for the Dushman reaction in the presence of H C l O 4 and N a C l O 4 . The impact of the reaction rate constant on the micromixing time calculation was investigated. An extension of the incorporation model for sulphuric acid is provided. Abstract: In order to characterize the efficiency of micromixing in chemical reactors, Villermaux used a borate buffer in the reaction system named after him. For micromixing time calculations, kinetic data of the Dushman reaction are essential. The choice of the acid and the influence of the salt on the reaction rate constant has led to a debate on the kinetics of the Dushman reaction. In the present work, a comprehensive kinetic study was performed to obtain the reaction rate equation of the Dushman reaction. A fifth-order rate equation with the partial reaction rate orders: H + 2; I O 3 - 1; I - 2 could be confirmed. Furthermore, the influence of ionic strength μ was investigated using sodium perchlorate as the ion source. The reaction rate constant k for the Dushman reaction was determined as a function of the ionic strength k = k 0 · f D u s h m a n log f D u s h m a n = - 1.93 ( ± 0.06 ) · μ 1 + μ + 0.40 ± 0.02 · μ . The impact of the newly obtained reaction rate constant on micromixing time calculations was investigated using the incorporation model. It could be shown, that micromixing times can differ by a power of ten depending on the chosen reaction rate constant. Moreover, an extension of the incorporation model for sulphuric acid is provided, which includes the acid dissociation constants. This model unites the obtained reaction rate constant from this work and the equilibrium reactions of sulphuric acid. Micromixing experiments can now be performed independent of the acid choice, since similar micromixing times are calculated. According to the CLP Regulation and REACH, boric acid is classified as toxic for reproduction. Therefore, non-toxic chemicals have recently been preferred which has led to the implementation of a phosphate buffer by Pinot et al. and Baqueiro et al. This has risen questions about the definition of the segregation index and micromixing time calculations. Comprehensive micromixing time calculations have been performed with an extended incorporation model for a phosphate buffer. The results suggest that both H P O 4 2 - and H 2 P O 4 - species only take partially part in the acid–base reaction.